Melatonin inhibits ethylene biosynthesis by regulating MdERF1/MdERF3 pathway during apple fruit ripening - Chen Li; Qian Yu; Yanmin Du; Wenhui Wang; Yajing Si; Yuling Liang; Shijiao Lin; Guangxin Yang; Weiting Liu; Aide Wang; Yinglin Ji (Postharvest Biology and Technology, 2026)

Changes of physicochemical, morphological, and biological properties of fucoidan from Monascus purpureus-fermented Undaria pinnatifida: Mechanisms and implications - Yuling Yang; Hong Lin; Xiaoting Fu (Food Hydrocolloids, 2026)

Modeling the cooling effects of urban rivers on surrounding built-up areas via a SOMUCH-based scaled outdoor experiment - Lin Liu; Xin Feng; Jian Hang; Jiajia Hua; Guanwen Chen; Qing Wu; Na Zhao; Yuguang Zhao; Yuling Yang (Sustainable Cities and Society, 2026)

Incorporating dynamic ozone stress and parameter optimization into the BEPS model for improved GPP simulation - Jian Wang; Yuling Du; Jibo Yue; Tianxiang Cui; Yumin Chen; Lin Sun; Lei Shi (Ecological Modelling, 2026)

Sustained-release salt reservoir enables durable solid electrolyte interphases for practical micron-sized silicon composite anodes - Kui Lin; Junke Wu; Zhengguang Song; Yuling Yi; Fuxi Peng; Shiwen Wang; Zhimin Zou; Tongbin Lan; Junxiong Wu; Chunhai Jiang (Chemical Engineering Journal, 2026)

The initiation and resuspension characteristics of (micro)plastics from varied depositional environments under hydraulic disturbance - Yuling Chen; Li Lin; Xiong Pan; Yuqi Zhang (Journal of Soils and Sediments, 2026)

Genome-wide characterization of the apple WOX family identifies MdWOX13 as a repressor of fruit ripening - Yinglin Ji; Shijiao Lin; Mingqian Wang; Yuling Liang; Meili Xin; Yanan Wang; Weiting Liu; Aide Wang; Bin Li (Postharvest Biology and Technology, 2026)

Optimized cryoablation and combinatorial chemotherapy overcome sublethal survival in pancreatic cancer cells - Yukun Cao; Xin Li; Jing Shen; Shanshan Xie; Haoyang Lin; Yuling Luo; Xinli Zhou (International Journal of Refrigeration, 2026)

Synthetic microbial community shields wheat from cadmium: Coordinating host metabolic reprogramming and rhizosphere microenvironment regulation - Huangxin Chen; Lin Kong; Yaoyuan Zhang; Guiyin Wang; Xin Qi; Changlian Xu; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Journal of Hazardous Materials, 2026)

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Nanomaterials in the food industry: applications and potential health risks - Wenrui Li; Suyu Lin; Luyao Zhang; Jiachen Yu; Yuling Cai; Di Wu; Yongning Wu; Guoliang Li (Food Chemistry, 2026)

Cellulose-based ultralight foam with dual-scale porosity from hybrid fibers for sustainable oil-water separation - Weiqiang Li; Jingge Liu; Meiying Li; Haitao Lin; Jian Fang; Xiaoqiao Wang; Jianchu Xu; Yuling Li; Junze Zhang; Xinheng Li; Gang Li (Carbohydrate Polymers, 2026)

Corrigendum to “Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum” [Geochim. Cosmochim. Acta 411 (2025) 233–249] - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2026)

Integrated non-targeted metabolomics, enzyme activities and morphological analysis to elucidate the mechanisms underlying the enhancement of activity and flavor of Monascus purpureus fermented Undaria pinnatifida - Yuling Yang; Hong Lin; Xiaoting Fu (Food Research International, 2026)

Identification, antioxidant and acetylcholinesterase inhibitory activities of soluble and insoluble-bioactive components from Cinnamomum camphora seed kernel residue - Pinpin Zhang; Junmin Long; Zheling Zeng; Xianghui Yan; Yujing Yang; Rongping Fu; Yuling Lin; Deming Gong; Cheng Zeng; Ping Yu (Food Research International, 2026)

Supramolecular calix[6]arene-COF with pocket-like cavities for host-guest recognition-based SERS detection of tryptamine and seafood freshness monitoring - Jiana Lin; Ying Chen; Gongke Li; Yuling Hu (Food Chemistry, 2026)

The Role of HIF-1α/BNIP3 Pathway in Hippocampal Neuronal Autophagy in Epilepsy - Huimin Kuang; Youshi Meng; Xinran Qin; Kai Qian; Chi Gong; Sijun Li; Lin Zhang; Xiaohang Gan; Yuling Lu; Yuan Wu (Molecular Neurobiology, 2026)

SFG enhances apoptosis of hepatocellular carcinoma by inhibiting tunneling nanotubes-mediated mitochondrial transport in the tumor microenvironment - Shasha Kong; Yuling Liu; Ruying Tang; Hui Li; Hongmei Lin; Longfei Lin (Apoptosis, 2026)

Bio-inspired fabrication of heterostructured porous core-shell PANI@Cu2O/CMC composite beads for green catalysis in A3 and decarboxylative A3 couplings - Shuyao Zhang; Ting Lin; Yuling Huang; Jiayi Huang; Meiling Xue; Zhihao Shan; Yiqun Li (Sustainable Chemistry and Pharmacy, 2025)

Revealing the spatial distribution of crown base height across China based on close-range Lidar data - Zekun Yang; Zhiyong Qi; Yuling Chen; Kai Cheng; Haitao Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Yu Ren; Weiyan Liu; Danyang Lin; Guoran Huang; et al. (Remote Sensing of Environment, 2025)

Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2025)

Zeolitic imidazolate frameworks exert bioenergetic modulation via the cAMP/PKA/CREB signaling pathway to accelerate periodontal regeneration - Weiqiang Hu; Xueshen Qian; Xuxin Lin; Qianqian Chen; Zekai Wu; Ziqin Chen; Zhenzhu Xue; Yuling Chen; Xiongcheng Xu; Kai Luo (Chemical Engineering Journal, 2025)

Divergent environmental controls on branched tetraethers along precipitation gradients in soils of the Tibetan Plateau - Yanwu Duan; Yuling Zhou; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Lin Chen; Yuanxin Li; Mengjing Li; Xianyong Cao; Fahu Chen (Chemical Geology, 2025)

Validating recent global canopy height maps over China's forests based on UAV lidar data - Ang Chen; Kai Cheng; Yuling Chen; Zhiyong Qi; Haitao Yang; Yu Ren; Zekun Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Guoran Huang; Tianyu Xiang; et al. (Remote Sensing of Environment, 2025)

KHDC3 affects the lineage differentiation of early embryo by regulating the differential distribution of YAP signal - Qian Xu; Yuling Lin; Lina Yu; Yang Zhang; Na Kong; Guijun Yan; Haixiang Sun; Guangyi Cao (Theriogenology, 2025)

Classification and identification of chicken-derived adulteration in pork patties: A multi-dimensional quality profile and machine learning-based approach - Hui Lu; Cong Yao; Lin An; Aiying Song; Feng Ling; Qiliang Huang; Yuling Cai; Yunguo Liu; Dacheng Kang (Food Control, 2025)

Dam operation changed the transport patterns of microplastics - from a global perspective - Yuling Chen; Li Lin; Yi Li; Yu Gao; Lei Dong; Xiong Pan; Ziwei Guo (Environmental Pollution, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Fermentation of Pyropia spp. seaweed: a comprehensive review on processing conditions, biological activities and potential applications in the food industry - Yuling Yang; Hong Lin; Xiaoting Fu (Critical Reviews in Food Science and Nutrition, 2025)

Impact of electric vehicle downsizing on shared mobility considering externalities - Li Li; Yuling Shi; Dianchao Lin; Yongliang Lu (Transportation Research Part D: Transport and Environment, 2025)

Efficient antibiotic tetracycline degradation and toxicity abatement via the perovskite-type CaFexNi1-xO3 assisted heterogeneous electro-Fenton system - Yuling Liang; Aochen Feng; Naif Abdullah Al-Dhabi; Jing Zhang; Wenle Xing; Tao Chen; Yuxuan Han; Guangming Zeng; Lin Tang; Wangwang Tang (Water Research, 2025)

Effective SSR markers for assessing population structure, genetic diversity, and volatile compounds in Atractylodis Rhizoma - Haotian Zhong; Lina Chen; Lei Chen; Xiao Huang; Ling Gong; Juan Hu; Yuling Zeng; Kun Yu; Lin Sen (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

Strychni Semen and two alkaloidal components cause apoptosis in HK-2 cells through TRADD-MAPK/NF-κB pathway - Wenyi Tian; Yuling Li; Fengzhi Liu; Hui Liu; Chen Li; Lin Bao; Xiaodong Liang (Toxicon, 2025)

An AP2/ERF transcription factor GhERF109 negatively regulates plant growth and development in cotton - Huiyun Shi; Ghulam Qanmber; Zuoren Yang; Yuling Guo; Shuya Ma; Sheng Shu; Yujun Li; Zhongxu Lin; Fuguang Li; Zhao Liu (Plant Science, 2025)

Host-guest mediated recognition and rapid extraction of Fusarium mycotoxins in cereals by nickel ferrite magnetic calix[4]arene-derived covalent organic framework fabricated in room-temperature - Jiana Lin; Gongke Li; Yuling Hu; Qisheng Zhong (Food Chemistry, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Effects of OSA-starch-fatty acid interactions on the structural, digestibility and release characteristics of high amylose corn starch - Mingyue Liu; Xiaoyan Wang; Yihui Li; Danni Jin; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Chemistry, 2024)

First wetland mapping at 10-m spatial resolution in South America using multi-source and multi-feature remote sensing data - Weiwei Sun; Gang Yang; Yuling Huang; Dehua Mao; Ke Huang; Lin Zhu; Xiangchao Meng; Tian Feng; Chao Chen; Yong Ge (Science China Earth Sciences, 2024)

The Footprints of Mitochondrial Fission and Apoptosis in Fluoride-Induced Renal Dysfunction - Qiyong Zuo; Lin Lin; Yuling Zhang; Mohammad Mehdi Ommati; Hongwei Wang; Jing Zhao (Biological Trace Element Research, 2024)

Rapid construction of double macrocycles, hierarchical covalent organic framework with size-sieving and host-guest recognition for selective adsorption and targeted analysis of mycotoxins in cereals - Zenghui Xie; Jiana Lin; Yuling Hu; Gongke Li; Qisheng Zhong (Chemical Engineering Journal, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

Early-relief effects of tetrahedral DNA nanostructures-assisted depression therapy via modulates hippocampal neurogenesis and neuroplasticity - Yikai Dou; Xiao Yang; Yue Du; Weitong Cui; Yuling Luo; Jinxue Wei; Liansheng Zhao; Xiaoxiao Cai; Xiaohong Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Plant regeneration in the new era: from molecular mechanisms to biotechnology applications - Chunli Chen; Yuxin Hu; Momoko Ikeuchi; Yuling Jiao; Kalika Prasad; Ying Hua Su; Jun Xiao; Lin Xu; Weibing Yang; Zhong Zhao; Wenkun Zhou; Yun Zhou; et al. (Science China Life Sciences, 2024)

Near-full-length genome analysis of two novel HIV second recombinant forms in Hebei, China - Yuxin Feng; Jianhua Lu; Lijing Wang; Yuling Wang; Jingyun Li; Hanping Li; Lin Li; Erhei Dai (Archives of Virology, 2024)

The photo- and microbial degradation kinetics and pathways of sulfadoxine in seawater elucidated by liquid chromatography coupled with time-of-flight mass spectrometry - Guowen Tang; Yuling Chen; Shanshan Lin; Xiaolin Li (Chemosphere, 2024)

Unveiling China’s natural and planted forest spatial–temporal dynamics from 1990 to 2020 - Kai Cheng; Haitao Yang; Hongcan Guan; Yu Ren; Yuling Chen; Mengxi Chen; Zekun Yang; Danyang Lin; Weiyan Liu; Jiachen Xu; Guangcai Xu; Keping Ma; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Well-known polypeptides of deer antler velvet with key actives: modern pharmacological advances - He Sun; Dandan Xiao; Wei Liu; Xue Li; Zhe Lin; Yong Li; Yuling Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Characterization, in vitro digestibility and release properties of starch-linoleic acid-sodium alginate composite film - Huirong Chen; Xiaoyan Wang; Danni Jin; Mingyue Liu; Xiaonian Wu; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Research International, 2023)

Calix[4]arene-based covalent organic frameworks with host-guest recognition for selective adsorption of six per- and polyfluoroalkyl substances in food followed by UHPLC-MS/MS detection - Zenghui Xie; Yuling Hu; Jiana Lin; Gongke Li; Qisheng Zhong (Journal of Hazardous Materials, 2023)

Genome-Wide Identification, Evolution Analysis of PI-PLC Family and Their Expression Patterns in Response to Different Hormones and Growth in Banana (Musa L.) - Qiuzhen Wu; Zhengyang Fan; Feng Qi; Dan Li; Zihao Zhang; Yukun Chen; Yuji Huang; Yuling Lin; Zhongxiong Lai (Tropical Plant Biology, 2023)

Correction to: Improving the specific activity and stability of alkaline pectinase PEL3 through SpyTag/SpyCatcher cyclization - Chao Du; Siqin Tan; Lin Liu; Yuling Zhou; Pan Wu; Guimin Zhang (Biotechnology Letters, 2023)

V-ATPase V0 subunit activation mediates maduramicin-induced methuosis through blocking endolysosomal trafficking in vitro and in vivo - Yuling Zheng; Jing Xiao; Junqi Wang; Bin Dong; Dawei Guo; Hui Ji; Haifeng Sun; Lin Peng; Shanxiang Jiang; Xiuge Gao (Food and Chemical Toxicology, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Effect of amylose content and crystal type on the structure and digestibility of starch-fatty acid complex nanoparticle - Mingyue Liu; Xiaonian Wu; Xiaoyan Wang; Yuling Jiang; Zhengyu Huang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Structure, 2023)

Improving the specific activity and stability of alkaline pectinase PEL3 through SpyTag/SpyCatcher cyclization - Chao Du; Siqin Tan; Lin Liu; Yuling Zhou; Pan Wu; Guimin Zhang (Biotechnology Letters, 2023)

Novel sensor array distinguishes heavy metal ions based on multiple fluorescence channels from dendritic mesoporous silica nanoparticles - Xiaotong Wu; Lei Tan; Yuling Li; Wanqiong Liu; Zhihua Peng; Yanshan Dong; Zeyu Huang; Lin Zhang; Yong Liang (Analytica Chimica Acta, 2023)

Corrigendum to “Novel diketopyrrolopyrrole NIR-II fluorophores and DDR inhibitors for in vivo Chemo-photodynamic therapy of Osteosarcoma” [Chem. Eng. J. 446 (2022) 136929] - Xiaoding Cheng; Chong Zhang; Kun Shen; Huifan Liu; Caihong Bai; Qihang Ding; Mengting Guan; Junzhu Wu; Zhiquan Tian; Deliang Chen; Lin Cai; Xuechuan Hong; et al. (Chemical Engineering Journal, 2023)

How rainfalls influence urban traffic congestion and its associated economic losses at present and in future: taking cities in the Beijing-Tianjin-Hebei region, China for example? - Yi Zhou; Sicheng Mao; Haile Zhao; Guoliang Zhang; Xin Chen; Yuling Jin; Lin Xu; Zhihua Pan; Pingli An; Fei Lun (Theoretical and Applied Climatology, 2022)

Research on Transfer Rate of Heavy Metals and Harmful Elements in Traditional Chinese Medicine Extraction and Refining Processes and Product Health Risk Assessment - Dujia Jin; Lin Li; Wujun Dong; Xiangyang Zhu; Xuejun Xia; Renyun Wang; Jun Ye; Ran Li; Zhihua Liu; Xueqing Xu; Lili Gao; Yuling Liu; et al. (Biological Trace Element Research, 2022)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Genome-Wide Identification and Comprehensive Analyses of TCP Gene Family in Banana (Musa L.) - Jessica Paola Sánchez Moreano; Xiaoping Xu; Cristina Belén Aucapiña Criollo; Xiaohui Chen; Yuling Lin; Nigarish Munir; Zhongxiong Lai (Tropical Plant Biology, 2021)

Molecular characterization of miRNA genes and their expression in Dimocarpus longan Lour - Yuling Lin; Yan Chen; Youjing Zeng; Shuting Zhang; Zihao Zhang; YuKun Chen; Jiawei Gong; Zhongxiong Lai (Planta, 2021)

TMEM166 inhibits cell proliferation, migration and invasion in hepatocellular carcinoma via upregulating TP53 - Jiejie Yang; Bin Wang; Qian Xu; Yuling Yang; Lin Hou; Kan Yin; Qingming Guo; Yanan Hua; Li Zhang; Yixuan Li; Jinyu Zhang; Ning Li (Molecular and Cellular Biochemistry, 2021)

MiR-221-3p regulates the microvascular dysfunction in diabetic retinopathy by targeting TIMP3 - Chongxian Wang; Yuling Lin; Yanqin Fu; Dongming Zhang; Yaping Xin (Pflügers Archiv - European Journal of Physiology, 2020)

Connecting gastrointestinal cancer risk to cadmium and lead exposure in the Chaoshan population of Southeast China - Xueqiong Lin; Lin Peng; Xijin Xu; Yanrong Chen; Yuling Zhang; Xia Huo (Environmental Science and Pollution Research, 2018)

Therapeutic potential of pro-angiogenic BPC157 is associated with VEGFR2 activation and up-regulation - Ming-Jer Hsieh; Hsien-Ta Liu; Chao-Nin Wang; Hsiu-Yun Huang; Yuling Lin; Yu-Shien Ko; Jong-Shyan Wang; Vincent Hung-Shu Chang; Jong-Hwei S. Pang (Journal of Molecular Medicine, 2017)

Cloning and expression analysis of betalain biosynthesis genes in Amaranthus tricolor - Xueli Zheng; Shengcai Liu; Chunzhen Cheng; Rongfang Guo; Yukun Chen; Liyang Xie; Yuyuan Mao; Yuling Lin; Zihao Zhang; Zhongxiong Lai (Biotechnology Letters, 2016)

Association between blood erythrocyte lead concentrations and hemoglobin levels in preschool children - Chunhua Liu; Xia Huo; Peng Lin; Yuling Zhang; Weiqiu Li; Xijin Xu (Environmental Science and Pollution Research, 2015)

In Vitro–In Vivo Correlations of Scalable PLGA-Risperidone Implants for the Treatment of Schizophrenia - Laura C. Amann; Michael J. Gandal; Robert Lin; Yuling Liang; Steven J. Siegel (Pharmaceutical Research, 2010)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)